Possible or not?

Calculus Level 3

Given that f ( x + y ) = f ( x ) f ( y ) f(x+y)=f(x)f(y) for all x , y R x,y \in \mathbb R , f ( x ) 0 f(x) \ne 0 , f ( 0 ) = 2 f'(0)=2 , and f ( 2 ) = 3 f(2)=3 .

Find f ( 2 ) f'(2) .

8 12 5 16 4 6 18

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Michael Huang
Dec 2, 2016

Let x x denote the variable of f f and y = 2 y = 2 . Then, f ( x + 2 ) = f ( x ) f ( 2 ) = 3 f ( x ) f(x + 2) = f(x)f(2) = 3f(x) By chain rule , f ( x + 2 ) = 3 f ( x ) f'(x + 2) = 3f'(x) Thus, if x = 0 x = 0 f ( 2 ) = 3 f ( 0 ) = 6 f'(2) = 3f'(0) = \boxed{6}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...